Local existence and uniqueness for a fractional SIRS model with Mittag-Leffler law - Sidi Ammi, Moulay Rchid (2021)
In this paper, we study an epidemic model with Atangana-Baleanu-Caputo (ABC) fractional derivative. We obtain a special solution using an iterative scheme via Laplace transformation. Uniqueness and existence of a solution using the Banach fixed point theorem are studied. A detailed analysis of the stability of the special solution is presented. Finally, our generalized model in the ABC fractional derivative sense is solved numerically by the Adams-Bashforth-Moulton method.